(untitled) (TEL Tempo, Espaço e Linguagem, 2024)
This article offers a reading of Femina: A New History of the Middle Ages, Through the Women Written Out of It (2022), by Janina Ramirez, focusing, as well, on the figure of Hildegard, one of the women treated by the author of this work, without intention enclose the possible debates from your reading. It is intended, as is so, to defend the importance of recognition and dissemination of stories produced by women and about women who live in different societies and times, aiming to contribute to a more holistic and inclusive understanding of history and society.